Bioabsorbable, elastomer-coated magnesium alloy coils for treating saccular cerebrovascular aneurysms. (November 2022) - Kim, Seungil; Nowicki, Kamil W.; Ye, Sangho; Jang, Kyeongwoo; Elsisy, Moataz; Ibrahim, Mohamed; Chun, Youngjae; Gross, Bradley A.; Friedlander, Robert M.; Wagner, William R.
Abstract: Cerebral aneurysm embolization is a therapeutic approach to prevent rupture and resultant clinical sequelae. Current, non-biodegradable metallic coils (platinum or tungsten) are the first-line choice to secure cerebral aneurysms. However, clinical studies report that up to 17% of aneurysms recur within 1 year after coiling, leading to retreatment and additional surgery. It would be ideal for the aneurysm coiling material to induce acute thrombotic occlusion, contribute to a tissue development process to fortify the degenerated vessel wall, and ultimately resorb to avoid leaving a permanent foreign body. With these properties in mind, a new fatty amide-based polyurethane urea (PHEUU) elastomer was synthesized and coated on biodegradable metallic (Mg alloy) coils to prepare a bioabsorbable cerebral saccular aneurysm embolization device. The chemical structure of PHEUU was confirmed using two-dimensional nuclear magnetic resonance spectroscopy. PHEUU showed comparable physical properties to elastomeric biodegradable polyurethanes lacking fatty amide immobilization, modest enzymatic degradation profiles in the first 8 wks, inherent antioxidant activity (>70% at 48 h), no cytotoxicity, and better protection for the underlying Mg alloy than poly(lactic- co -glycolic acid) (PLGA) against surface corrosion and cracking. Rat aortic smooth muscle cell attachment and platelet deposition were higher with the PHEUUs compared to bare or PLGA coated Mg alloy in vitro. PHEUU-coated Mg alloy coils showed the potential to design a fully bioabsorbable embolization coil amenable to clinical placement conditions based on computational mechanics modeling and blood-contacting test using an in vitro aneurysm model. In vivo studies using a mouse aneurysm model elicited comparable inflammatory cytokine expression to a commercially available platinum coil.